1996
DOI: 10.1007/bf02437839
|View full text |Cite
|
Sign up to set email alerts
|

Biodemographic comparisons of homosexual and heterosexual men in the kinsey interview data

Abstract: Relations between sexual orientation and several biodemographic variables previously reported to differentiate between homosexual and heterosexual men were examined. Subjects were 4948 white, postpubertal males, who were never reared in foster homes, orphanages, or other institutions, and were never arrested or convicted on criminal charges. These were dichotomously classified as homosexual (n = 844) or heterosexual (n = 4104). Data came from survey interviews conducted by staff members of The Kinesey Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 68 publications
3
63
1
Order By: Relevance
“…Finally, note that most of our prior studies found no difference between heterosexual and homosexual men in parental (e.g., maternal) age or found that an older parental age in homosexual samples was probably a consequence of a late (fraternal) birth order (8,9,23). That homosexual men in the present study had younger (and not older) mothers relative to the heterosexual men provides additional support that the fraternal birth-order effect does not occur because of a potential confounding influence of an elevated parental age in the mothers of homosexual men.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Finally, note that most of our prior studies found no difference between heterosexual and homosexual men in parental (e.g., maternal) age or found that an older parental age in homosexual samples was probably a consequence of a late (fraternal) birth order (8,9,23). That homosexual men in the present study had younger (and not older) mothers relative to the heterosexual men provides additional support that the fraternal birth-order effect does not occur because of a potential confounding influence of an elevated parental age in the mothers of homosexual men.…”
Section: Resultsmentioning
confidence: 70%
“…The most consistent biodemographic correlate of sexual orientation in men is the number of older brothers, originally observed by Blanchard and Bogaert (8) in a Canadian sample in the 1990s but since then found in samples from different eras and from different countries, both by us and independent investigators (2,7,(9)(10)(11)(12). Evidence does not exist that sibling characteristics reliably correlate with women's sexual orientation (13,14).…”
mentioning
confidence: 88%
“…One mechanism for this is the maternal immune hypothesis, which proposes that the accumulating antibodies to male specific antigens with each successive male fetus carried results in feminizing of the male brain leading to homosexuality (Blanchard & Bogaert 1996). FBO is considered the most reliable biodemographic correlate of sexual orientation, but it cannot account for all the variation since there are gay men with no older brothers (Zucker, Blanchard, Kim, Pae, & Lee, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the full samples for Blanchard and Bogaert (1996b) and Blanchard and Lippa (2007), the homosexual groups had larger numbers of total siblings; in the firstborn subsamples from these same studies, the homosexual groups had smaller numbers of younger siblings. In the full sample for Blanchard and Bogaert (1996a), the homosexual and heterosexual groups had virtually identical numbers of total siblings; in the firstborn subsample from this study, the homosexual group had a smaller number of younger siblings than the heterosexual group.…”
Section: Resultsmentioning
confidence: 93%
“…This section of this article presents some more specific information about the subjects from which the firstborn subgroups were drawn. Blanchard and Bogaert (1996a) These authors investigated birth order in a subsample age 18 and older to minimize any possible distorting effects of incomplete sibships (Blanchard & Bogaert, 1996a, p. 560). The mean number of siblings (older brothers ?…”
Section: Methodsmentioning
confidence: 99%